Influence of Size and Geometry on Magnetic Core Losses - Puyal Ventura, Alex; Pérez Cebolla, Francisco José; Herrero Gracia, Lucas; Bernal Ruiz, Carlos (Jornada de Jóvenes Investigadores del I3A, 2025)
This paper analyzes the possible influence of the size and geometry of the magnetic core on the determination of volume losses under identical excitation conditions. Three types of cores made of the same material are evaluated over a wide range of frequencies using an experimental test bench built for this purpose.